Drug holidays: the most frequent type of noncompliance with calcium plus vitamin D supplementation in persistent patients with osteoporosis - Touskova, Tereza; Vytrisalova, Magda; Palicka, Vladimir; Hendrychova, Tereza; Fuksa, Leos; Holcova, Radka; Konopacova, Jana; Kubena, Ales Antonin (Patient preference and adherence, 2015)
PURPOSE: All current recommendations include calcium and vitamin D (Ca-D) as an integrated part of osteoporosis treatment. The purpose of this pilot study was to analyze compliance with a fixed combination of Ca-D in women persistent with the treatment. PATIENTS AND METHODS: An observational study was carried out in three osteocenters in the Czech Republic. Women with osteoporosis ≥55 years of age concurrently treated with oral ibandronate were eligible. Compliance was evaluated in a period of 3 months by Medication Event Monitoring System (MEMS), tablet count, and self-report. Nonpersistence was defined as a MEMS-based gap in the use of Ca-D to be 30 days or more. RESULTS: A total of 73 patients were monitored, of which 49 patients were analyzed (target population). Based on MEMS, mean overall compliance was 71%; good compliance (≥80%) was observed in 59% of the patients. As many as 71% of the patients took drug holidays (≥3 consecutive days without intake); overall compliance of these patients was 59% and was slightly lower on Fridays and weekends. Patients without drug holidays were fully compliant (did not omit individual doses). Compliance differed according to daily time at which the patients mostly used the Ca-D. Afternoon/evening takers showed a mean overall compliance of 82% while morning/night takers only 51% (P=0.049). Based on MEMS, tablet count, and self-report, compliance ≥75% was observed in 59%, 100%, and 87% of the patients, respectively. Outcomes obtained by the three methods were not associated with each other. Undesirable concurrent ingestion of Ca-D and ibandronate was present only twice. CONCLUSION: Despite almost perfect self-reported and tablet count-based compliance, MEMS-based compliance was relatively poor. Consecutive supplementation-free days were common; more than two-thirds of the patients took at least one drug holiday. This pilot study showed drug holiday to be the most important type of noncompliance with Ca-D in those who are persistent with the treatment.
Keywords: drug holidays; osteoporosis; medication adherence; calcium supplementation; self-report; Medication Event Monitoring System (MEMS); patient compliance